Biologics and Non-Biologics Immunosuppressive Treatments for IgA Nephropathy in Both Adults and Children - Chiarenza, Decimo Silvio; Verrina, Enrico Eugenio; La Porta, Edoardo; Caridi, Gianluca; Ghiggeri, Gian Marco; Mortari, Gabriele; Lugani, Francesca; Angeletti, Andrea; Bigatti, Carolina (Journal of clinical medicine, 2024)
Immunoglobulin A nephropathy represents the most prevalent cause of glomerulonephritis worldwide and may lead to renal failure in a relevant number of cases in both paediatric and adult subjects. Although their pathogenesis is still largely unclear, evidence of immune abnormalities provides the background for the use of immunosuppressive drugs, such as corticosteroids, calcineurin inhibitors, and antiproliferative and alkylating agents. Unfortunately, these treatments fail to achieve a sustained remission in a significant percentage of affected patients and are burdened by significant toxicities. Recent developments of new biologics, including anti-BAFF/APRIL inhibitors and molecules targeting complement components, offered the opportunity to selectively target immune cell subsets or activation pathways, leading to more effective and safer hypothesis-driven treatments. However, studies testing new biologic agents in IgAN should also consider paediatric populations to address the unique needs of children and close the therapeutic gap between adult and paediatric care.